A Cognitive Learning Account of the Avoidance, Omission and Exaggerated Phenomena and Expressions in Young Adolescents' Drawings of the Human Figure in the Visual Culture Art Education Context. (12th July 2020) - Lau, Chung‐yim
Abstract: It is common in the everyday art class to find many examples of avoidance, omission and exaggeration in young adolescents' depictions of the human figure. When students depict sophisticated human images, they make every effort to avoid the difficult parts, and some students tend to exaggerate the size or distort the shape of the human image. Art educators see these types of behaviour and modes of expression as unnatural, and claim that they may hinder the development of the creativity of young adolescents. Relevant discussions in the literature from a psychological perspective are mainly concerned with the negative impact of such behaviour and modes of expression on the formation of young adolescents' identities. However, in the context of popular visual culture, the findings of recent studies on young adolescents' comic drawings have suggested that when young adolescents draw comic characters, they use their everyday life experiences in their drawings. This article reports on a five‐year qualitative longitudinal study conducted in a Hong Kong secondary school. The aim of the study was to deepen our understanding of this behaviour on the part of adolescents in art classes. The findings of the study confirmed the view that these aspects should be interpreted from a cognitive learning perspective. It is suggested that art educators reconsider these types of behaviour and modes of expression as a potential means for improving secondary students' learning of the art of popular visual culture.